Outbreak of Candida lusitaniae bloodstream infection in neonatal intensive care unit: case series - Sri Kusuma Dewi, Ida Ayu; Saputra, I Wayan Agus Gede Manik; Tanaya, Putu Wahyu Dyatmika; Tangkas, Made Refika Widya Apsari; Mahendra, I Putu; Handayani, Lidya (Journal of Clinical Microbiology and Infectious Diseases, 2025)
Introduction: Neonatal sepsis remains a significant health challenge, particularly in low- and middle-income countries (LMICs), where inadequate healthcare infrastructure and sanitation contribute to its high incidence. Sepsis is defined as life-threatening organ dysfunction resulting from a dysregulated immune response to infection. Neonates are particularly vulnerable due to immature immune systems. Candida species, especially Candida albicans and Candida parapsilosis, are common pathogens, but Candida lusitaniae has also emerged as a notable cause of neonatal sepsis, with increased resistance to Amphotericin B. This case series highlights an outbreak of Candida lusitaniae bloodstream infections in a neonatal intensive care unit (NICU), emphasizing the diagnostic and management challenges of rare fungal infections. Case Description: In this report, we describe five neonatal sepsis cases caused by Candida lusitaniae in our NICU. All patients exhibited respiratory distress, pneumonia, and elevated procalcitonin levels, and were treated with Voriconazole. The neonates had varying risk factors, including prematurity, low birth weight, and asphyxia. Blood cultures identified Candida lusitaniae in all cases, with susceptibility testing confirming sensitivity to Voriconazole, Amphotericin B, and Flucytosine. Environmental sampling revealed contamination in the NICU, specifically from a sink, suggesting nosocomial transmission. In response, the NICU was decontaminated, infection control protocols were reinforced, and environmental surveillance was intensified. All patients improved clinically and were discharged without major complications, except for mild encephalopathy in one case. Conclusion: This outbreak underlines the importance of timely identification and appropriate therapy in managing rare fungal infections in neonates. It also highlights the critical role of environmental sources in nosocomial infections and the need for robust infection control measures in NICUs. Strict infection prevention strategies, including enhanced cleaning, staff training, and surveillance, are essential to preventing such outbreaks in high-risk settings.